Neutralizing Activity and SARS-CoV-2 Vaccine mRNA Persistence in Serum and Breastmilk After BNT162b2 Vaccination in Lactating Women - Yeo, Kee Thai; Chia, Wan Ni; Tan, Chee Wah; Ong, Chengsi; Yeo, Joo Guan; Zhang, Jinyan; Poh, Su Li; Lim, Amanda Jin Mei; Sim, Kirsten Hui Zhi; Sutamam, Nursyuhadah; Chua, Camillus Jian Hui; Albani, Salvatore; et al. (Frontiers in Immunology, 2022)
Background: There is limited information on the functional neutralizing capabilities of breastmilk SARS-CoV-2-specific antibodies and the potential adulteration of breastmilk with vaccine mRNA after SARS-CoV-2 mRNA vaccination. Methods: We conducted a prospective cohort study of lactating healthcare workers who received the BNT162b2 vaccine and their infants. The presence of SARS-CoV-2 neutralizing antibodies, antibody isotypes (IgG, IgA, IgM) and intact mRNA in serum and breastmilk was evaluated at multiple time points using a surrogate neutralizing assay, ELISA, and PCR, over a 6 week period of the two-dose vaccination given 21 days apart. Results: Thirty-five lactating mothers, median age 34 years (IQR 32-36), were included. All had detectable neutralizing antibodies in the serum immediately before dose 2, with significant increase in neutralizing antibody levels 7 days after this dose (median 168.4 IU/ml (IQR 100.7-288.5) compared to 2753.0 IU/ml (IQR 1627.0-4712.0), p <0.001). Through the two vaccine doses, all mothers had detectable IgG1, IgA and IgM isotypes in their serum, with a notable increase in all three antibody isotypes after dose 2, especially IgG1 levels. Neutralizing antibodies were detected in majority of breastmilk samples a week after dose 2 (median 13.4 IU/ml (IQR 7.0-28.7)), with persistence of these antibodies up to 3 weeks after. Post the second vaccine dose, all (35/35, 100%) mothers had detectable breastmilk SARS-CoV-2 spike RBD-specific IgG1 and IgA antibody and 32/35 (88.6%) mothers with IgM. Transient, low intact vaccine mRNA levels was detected in 20/74 (27%) serum samples from 21 mothers, and 5/309 (2%) breastmilk samples from 4 mothers within 1 weeks of vaccine dose. Five infants, median age 8 months(IQR 7-16), were also recruited - none had detectable neutralizing antibodies or vaccine mRNA in their serum. Conclusion: Majority of lactating mothers had detectable SARS-CoV-2 antibody isotypes and neutralizing antibodies in serum and breastmilk, especially after dose 2 of BNT162b2 vaccination. Transient, low levels of vaccine mRNA were detected in the serum of vaccinated mothers with occasional transfer to their breastmilk, but we did not detect evidence of infant sensitization. Importantly, the presence of breastmilk neutralising antibodies likely provides a foundation for passive immunisation of the breastmilk-fed infant.